Drug-Related Identity Change - ferydoon Seyed Rabiee (Drug Control Headquarters, Research and Education Office, 2004)
Our study is concentrating on understanding drug-related identity process which may enter important sociological visions into drug abuse pathology. It is in the framework of symbolic proactivity، cultural studies and the existing model for analyzing drug-related identity (Anderson - 1994). In this study، we have used a qualitative survey and a model test in a statistical sample cosisting white/black males and females who are under drug abuse treatment in Middle Michigan. Our data shows that identity change occures during childihood or early adolescence and is accompanied with experiences of isolationism before drug abuse which facilitates the creation of an afflicted identity as well as the loss of the ability to control the personal identity. Assimilation and drug abuse subculture have represented altenative identities for resolving such an unsuitable situation.